2012
DOI: 10.1016/j.fcr.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Research achievements and adoption of no-till, dryland cropping in the semi-arid U.S. Great Plains

Abstract: The Great Plains region of the United States is an area of widespread dryland crop production, with wheat being the dominant crop. Precipitation in the region ranges from 300 to 500 mm annually, with the majority of precipitation falling during hot summer months. The prevailing cropping system is a two-year rotation of wheat and summer fallow. The adoption of no-till practices has resulted in greater precipitation storage and use efficiency, which has led to greater cropping intensity, higher productivity, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
157
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 45 publications
3
157
1
1
Order By: Relevance
“…Moreover, when fallow is eliminated, C inputs are increased due to a higher production of biomass which enhances the amount of SOC sequestered (Álvaro-Fuentes et al 2009b;Virto et al 2012). However, in areas with a high water deficit, the benefits of using cover crops as green manure are offset by water lost for subsequent cash crops (Hansen et al 2012). The use of legumes as green manure could also have a detrimental impact on SOC as it has been discussed in the previous section.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, when fallow is eliminated, C inputs are increased due to a higher production of biomass which enhances the amount of SOC sequestered (Álvaro-Fuentes et al 2009b;Virto et al 2012). However, in areas with a high water deficit, the benefits of using cover crops as green manure are offset by water lost for subsequent cash crops (Hansen et al 2012). The use of legumes as green manure could also have a detrimental impact on SOC as it has been discussed in the previous section.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 96%
“…Many studies have pointed out the inefficiency of this practice in terms of water storage. Thus, the works by Lampurlanés et al (2002) and Hansen et al (2012) showed that only 10-35 % of the rainfall received was available for the next crop when fallow was included in the rotation. Water is lost during fallow periods due to evaporation given (i) the low amount of residues covering the soil surface and (ii) the frequent use of tillage to eliminate weeds in most of the dryland agroecosystems.…”
Section: Adoption Of More Efficient Water Management Practicesmentioning
confidence: 99%
“…Here reduced fallow periods in areas of shifting cultivation without concomitant adoption of modern management practices 15 , or non-introduction/adoption of nonlocal but high-yielding maize seeds by farmers 16 , may be responsible. In the United States, greater adoption of no-till practice by farmers in the semi-arid areas of the Great Plains has coincided with intensified crop rotations 17 (for example, wheatmaize rotations as opposed to a fallow following wheat). Farmer net incomes may have consequently increased, but intensified crop rotations may have also led to increased yield variability and crop failures 17 in an area of already limited water resources 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, greater adoption of no-till practice by farmers in the semi-arid areas of the Great Plains has coincided with intensified crop rotations 17 (for example, wheatmaize rotations as opposed to a fallow following wheat). Farmer net incomes may have consequently increased, but intensified crop rotations may have also led to increased yield variability and crop failures 17 in an area of already limited water resources 18 . Our analysis shows widespread yield stagnation in these regions, especially for wheat (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crop intensification, diversification, reduced tillage, and variable N management are among the strategies proposed to mitigate and adapt monocultures to projected climate shifts (Burney et al, 2010;Smith and Olesen, 2010;Tilman et al, 2011;Powlson et al, 2014;Ponisio et al, 2015). Diversifying crop options may increase the resiliency of agroecosystems (Lin, 2011) and stabilize cropping systems vulnerable to a changing climate (Altieri et al, 2015) through agronomic (Johnston et al, 2005;Kirkegaard et al, 2008;Hansen et al, 2012;Seymour et al, 2012;Cutforth et al, 2013;Angus et al, 2015), economic (Entz et al, 2002;Zentner et al, 2002bZentner et al, , 2004, and environmental Gan et al, 2011;Davis et al, 2012) benefits. In the summer-dominate precipitation region of the North American Great Plains, soil conservation practices have enabled crop intensification through fallow replacement (Lafond et al, 1992;Anderson et al, 2003), which has increased opportunities to diversify crops (Halvorson et al, 1999;Zentner et al, 2002b;Tanaka et al, 2005;Roberts and Johnston, 2007), enhance N and water use efficiencies (Pikul et al, 2012).…”
mentioning
confidence: 99%